Experimental study of geotextiles for karst subgrade collapse under static and dynamic loads - Wu, Di; Yi, Yang; Chen, Qingshu; Wu, Jing; Yang, Yanxin; Wu, Jianjian; Amin, Ruhul (Frontiers in Earth Science, 2025)
IntroductionKarst subgrade collapse has the characteristics of suddenness and concealment, which poses a major challenge to the stability of infrastructure.MethodsA scale model test was designed to investigate the effects of different reinforcing conditions and different loading modes on the load transfer and distribute of reinforced cushions, with emphasis on monitoring the vertical pressure, internal fill and surface displacements in the subsided area and the stable area during the collapse process.ResultsThe results show that during subsidence, vertical stresses decrease in the subsidence area and increase in the stable area. The load affects the soil arch effect, with dynamic loads having a greater impact on soil stability compared to static load and unloaded conditions. Geotextile reinforcement enhances the soil arch and tensile membrane effects, reducing vertical displacement by 5.58%–10.95% under dynamic loads and by 34.76%–66.56% under static load and unloaded.DiscussionThis research provides theoretical and experimental support for geotextile reinforcement design in karst subsidence, helping to prevent karst collapse.